2021
DOI: 10.1016/j.anai.2021.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion after coronavirus disease 2019 vaccination in patients with immune deficiency

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 12 publications
(6 reference statements)
2
30
1
Order By: Relevance
“…All but the patient with X-linked agammaglobulinemia were able to produce specific anti–SARS-CoV-2 spike protein antibodies, suggesting that patients with antibody deficiency are able to respond to the vaccine. 6 That said, we agree that further data with larger-scale studies and longer duration of follow-up are required.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…All but the patient with X-linked agammaglobulinemia were able to produce specific anti–SARS-CoV-2 spike protein antibodies, suggesting that patients with antibody deficiency are able to respond to the vaccine. 6 That said, we agree that further data with larger-scale studies and longer duration of follow-up are required.…”
mentioning
confidence: 72%
“…Kinoshita et al recently described a robust immune response after COVID-19, with 4 of 5 patients generating a humoral immune response despite their underlying antibody deficiency. 5 Similarly, Squire and Joshi 6 evaluated the humoral immune response to mRNA COVID-19 vaccine in 10 patients with underlying primary immune deficiency. Their cohort included 6 patients with CVID, 1 patient with hypogammaglobulinemia, 1 patient with Wiskott-Aldrich syndrome, 1 patient with 22q11.2 deletion syndrome, and 1 patient with X-linked agammaglobulinemia.…”
mentioning
confidence: 99%
“…Even patients with PIDs and SIDs do not seem to have contraindications to COVID-19 vaccines. In fact, no higher frequency of AEs was observed in two preliminary studies, the first one on 11 immune deficient patients (10 PIDs and 1 SID) [98] and the other on 26 patients with inborn errors of immunity (26 PIDs) [99], where substantial safety of the mRNA Pfizer vaccine and satisfactory immunogenicity was observed, except for the four patients with X-linked agammaglobulinemia, in whom an adaptive cellular response was observed. A recent study confirmed the lack of antibody response in patients with X-linked agammaglobulinemia, compensated by the induction of an adaptive cellular response, whereas the response of patients with Common Variable Immunodeficiency was found to be unsatisfactory and non-protective at both cellular and humoral levels [100].…”
Section: Safety Of Covid-19 Vaccines In Patients With Aiaids Pids and Sidsmentioning
confidence: 94%
“…* The risk-benefit evaluation of temporary immunosuppressive treatment interruption should be done by the immunology specialist based on the clinical picture. Regarding PIDs, the presence of Ig replacement therapy does not seem to have interfered with the cellular and humoral immune response observed in most patients, except for patients with X-linked agammaglobulinemia, who did not show antibody response, but were protected by the adaptive cellular immunity[98,99]. However, immunoglobulin for intravenous (IVIg) or subcutaneous (SCIg) use should not be administered in the same time period as vaccination, because it is impossible to check the humoral vaccine response, given that IVIg/SCIg may contain different concentrations of anti-SARS-CoV-2 antibodies[115,116].…”
mentioning
confidence: 94%
See 1 more Smart Citation